2022
DOI: 10.3390/ijms232012244
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Influenza Viruses—Drug Resistance, Treatment Options, and Prospects

Abstract: Viral evolution refers to the genetic changes that a virus accumulates during its lifetime which can arise from adaptations in response to environmental changes or the immune response of the host. Influenza A virus is one of the most rapidly evolving microorganisms. Its genetic instability may lead to large changes in its biological properties, including changes in virulence, adaptation to new hosts, and even the emergence of infectious diseases with a previously unknown clinical course. Genetic variability ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 97 publications
0
23
0
Order By: Relevance
“…It has also been concluded that resistance is largely due to the spread of a single variant [ 40 ]. Now, more than 10 years after this discovery, knowledge about not only the phenomenon of drug resistance, but also new anti-influenza drugs, vaccinations, or the genetics of the influenza virus itself, has significantly increased through the work of scientists and medical doctors [ 41 , 42 ]. Assessment of the susceptibility of currently circulating influenza viruses to antivirals is an important element of influenza virological surveillance required by the WHO, which the National Influenza Centers are trying to fulfill [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been concluded that resistance is largely due to the spread of a single variant [ 40 ]. Now, more than 10 years after this discovery, knowledge about not only the phenomenon of drug resistance, but also new anti-influenza drugs, vaccinations, or the genetics of the influenza virus itself, has significantly increased through the work of scientists and medical doctors [ 41 , 42 ]. Assessment of the susceptibility of currently circulating influenza viruses to antivirals is an important element of influenza virological surveillance required by the WHO, which the National Influenza Centers are trying to fulfill [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral resistance is a natural phenomenon often caused by viral evolution. Nonetheless, evidence indicates an increase in drug resistance due to drug-induced selective pressure [ 66 , 177 , 178 ], propped by inappropriate use and excessive prescription [ 67 , 179 ]. The same applies to the use of antibiotics and development of antimicrobial resistance [ 68 , 180 ].…”
Section: The Role and Value Of Rapid Testing For The Management And T...mentioning
confidence: 99%
“…In the absence of a conclusive diagnosis, physicians often opt to prescribe antibiotics as a preventive rather than treatment measure [ 179 ]. Timely access to differential diagnosis might help improve patient treatment stewardship and, in turn, help reduce the risks of antibiotic resistance at individual and population levels [ 31 , 66 , 67 ]. A study found that in positive influenza cases, rapid diagnostic testing reduced unnecessary antibiotic prescriptions, and in negative cases, prompted the adequate treatment of bacterial infections [ 31 ].…”
Section: The Role and Value Of Rapid Testing For The Management And T...mentioning
confidence: 99%
“…For example, the writings of Hippocrates in 412 BCE describing the “Cough of Perinthus” suggest that this may have been an influenza-like outbreak [ 10 , 11 ]. When reflecting on the past century, a total of four influenza-related pandemics have occurred: the 1918 A/H1N1 pandemic, which is misnomered as the “Spanish Flu,” the 1957 A/H2N2 reassortant human and avian virus that emerged in China, the 1968 A/H3N2 Hong Kong influenza, and the new A/(H1N1)pdm09 variant that first appeared in North America in the April of 2009 [ 12 ]. In each of these four pandemics, at least 10,000 lives were lost, and developing universal influenza vaccines has become a necessity.…”
Section: Influenza Virusmentioning
confidence: 99%